Unconsciously competing goals can collaborate or compromise as well as win or lose. Issue 2 (29th April 2014) - Carruthers, Peter
Abstract This commentary offers a friendly extension of Huang & Bargh's (H&B's) account. Not only do active goals sometimes operate unconsciously to dominate or preempt others, but simultaneously active goals can also collaborate or compromise in shaping behavior. Because neither goal wins complete control of behavior, the result may be that each is only partly satisfied.